The Comprehension of Metaphorical Descriptions Conveying Gender Stereotypes. An Exploratory Study - Borelli, Eleonora; Cacciari, Cristina (Frontiers in Psychology, 2019)
In this adjective elicitation study, we investigated the comprehension of Italian sentences where a metaphorically intended noun (e.g., butterfly, nightmare) was used to describe a gender-stereotyped or stereotype-neutral individual (e.g., flute player, engineer, person). Specifically, we explored whether and to what extent meaning availability and the affective valence of these metaphorical descriptions (e.g., This flute player is a butterfly) varied as a function of the stereotypical or stereotype-neutral nature of the sentential subject, the male vs. female direction of the stereotype, and the grammatical gender marked in the subject noun phrase. Our goals were to test whether the meaning of metaphorical descriptions was equally available regardless of the presence and direction of the gender stereotype and of the grammatical gender of the subject, and whether the adjectives expressing the sentential meaning had the same affective valence no matter who was the subject. The results showed that it was easier (i.e., more adjectives came up to mind) to express the sentence meaning when the sentences described male stereotyped individuals than female stereotyped or stereotype-neutral individuals. The adjective valence did not significantly change according to the subject type. Participants produced adjectives with the wrong grammatical gender more often for males in stereotypically female occupations than for females in stereotypically male occupations. These gender errors occurred also when the sentences described females engaged in stereotypically female occupations. Overall, these results extend to metaphorical descriptions previous findings showing that a social group (males) is seen as more normative than another (females), and acts as the unmarked normative group.